OPERATIONS MANAGEMENT ASPECTS AT PRODUCTION ENTERPRISE - Berisha, Aferdita Dervishi (European Scientific Journal, ESJ, 2012)
In this paper are analyzed the operation aspects of a production enterprise “Natyra-Rol” that is dealing with the production of different blinds. The purpose of this paper is to identify the preferences and deficiencies of operations at “Natyra-Rol”; to analyze the supply chain; the production process; the store, distribution and sale; quality management and marketing. In this paper is used inductive method, by using primary source to gather data and through quality research, where as a technique of gathering primary data is used half structured questionnaire. As secondary source is used literature, to analyze the theoretical aspects of operations and its practical intercommunication at “Natyra-Rol”. Based on findings it is ascertained that enterprise “Natyra-Rol” is rentable and is developing its production and business activity only inside Kosovo. From the point of view of Operations Management, the activities of enterprise are focused on operational level. In order to achieve performance and competition in the market, the enterprise should adopt measures to produce cost-benefit; to have production plan and strategic plan for marketing.